Efforts to increase growth and brix level of various varieties of sorghum (Sorghum bicolor L.) through additive intercropping with peanut - Toibba, Huswatun; Wangiyana, Wayan; Zubaidi, Akhmad (Universitas Muhammadiyah Mataram, 2023)
Intercropping with legumes was reported to increase growth and yield components of cereal crops. To determine the effect of additive intercropping with peanut on growth and stem brix level of various varieties of sorghum (Sorghum bicolor L.), a pot experiment was carried out from September 2021 to January 2022 in plastic house, which were arranged according to a Completely Randomized Design consisting of two factors with three replications. The first factor was intercropping (T0: sorghum monocrop, T1: sorghum inserted with peanuts), and the second factor was sorghum varieties (V1: Latu Keta, V2: Gando Bura, V3: Gando Keta, V4: Samurai-2). Data were analyzed with analysis of variance (ANOVA) and Tukey's HSD at 5% significance level using Costat for Windows ver. 6.303. The results showed that intercropping only significantly increased plant height (42 and 56 DAP), number of leaves (42 and 56 DAP), and growth rate of leaf number, when compared with monocrop sorghum, whereas differences in varieties affected almost all observed variables, except number of leaves 28 DAP. However, there was an interaction effect of the treatment factors (T*V) on plant height at 56 DAP, growth rate of plant height, and number of leaves at 42 DAP. Intercropping significantly increased plant height and leaf number in Gando Bura and Gando Keta varieties, but the increase in stem brix content due to intercropping was significant only in Gando Bura variety. Further research in the field is needed for better results from the real farms.